KEANEKARAGAMAN KUMBANG CERAMBYCIDAE (COLEOPTERA) DI KAWASAN GUNUNG MEKONGGA DESA TINUKARI KECAMATAN WAWO KABUPATEN KOLAKA UTARA PROVINSI SULAWESI TENGGARA(Diversity Of Cerambycidae Beetle (Coleoptera) In Mekongga Mount Area, In Tinukari Village Wawo Sub D - ., Amirullah; Ariani, Citra; ., Suriana (Jurnal BioWallacea, 2014)
The aim of this research is to determine the distribution, diversity, evenness and similarity of Cerambycidae bettle based on the total of species and individual at different altitude in mount of Mekongga area in Tinukari village Wawo sub district, north Kolaka regency in South East Sulawesi province. This research was used a survey method, catching Cerambycidae bettle by using sweep net, light trap, malaise trap, artocarpus trap and yellow pan trap by TCBG-LIPI mekongga team. Mounting and identification in laboratory entomology, sector zoology, biology research center Tndonesian of science, Cibinong Bogor, west java. The result show that there are 3 subfamilies of Cerambycidae bettle; Laminae (54 species), Cerambycidae (21 species) and Prioninae (1 species). The highest diversity index, was found at 0-500 asl (H=3,389) and the evennes high category was found at 1000-1500 asl (H=1). The highest similarity index of species was found at 0-500 and 500-1000 asl (47,225%). Â Key words : Cerambycidae Bettle, Diversity, Mekongga Mount.